Are female skins sold for a lower price? Evidence from the Fortnite game - Georg Stadtmann; Aynur Dilan Tosun; Christian Pierdzioch (European University Viadrina, Department of Business Administration and Economics, 2020)
Much significant research has been done to shed light on discrimination of females in, for example, labor markets. Less is known, in contrast, about the amount of discrimination in the virtual world of online gaming. In an early study, Castronova (2004) finds that female avatars receive about 10% lower prices in online auctions. In this research note, we re-examine the pricing of avatars sold in the Fortnite game. We cannot reject the null hypothesis that female and male avatars are sold at the same prices. We also account for the impact of a Fortnite sex scandal on the price differential between female and male avatars.
Keywords: J16; L11; M31; 330; gender discrimination; Fortnite; gaming; Freemium; product differentiation; market segmentation